Comparison of Estimated Severe Acute Respiratory Syndrome Coronavirus 2 Seroprevalence Through Commercial Laboratory Residual Sera Testing and a Community Survey. (10th December 2020) - Bajema, Kristina L; Dahlgren, F Scott; Lim, Travis W; Bestul, Nicolette; Biggs, Holly M; Tate, Jacqueline E; Owusu, Claudio; Szablewski, Christine M; Drenzek, Cherie; Drobeniuc, Jan; Semenova, Vera; Li, Han; et al.
Abstract: We compared severe acute respiratory syndrome coronavirus 2 seroprevalence estimated from commercial laboratory residual sera and a community household survey in metropolitan Atlanta during April and May 2020 and found these 2 estimates to be similar (4.94% vs 3.18%). Compared with more representative surveys, commercial sera can provide an approximate measure of seroprevalence.